Pengaruh Variasi Produk, Word of Mouth, Dan Gaya Hidup Terhadap Minat Beli Emas (Studi Kasus Konsumen Toko Emas Mahkota) - Arif, Pandu Imansyah; Widarko, Agus; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine the influence of product variations, word of mouth, and lifestyle on interest in buying gold, with a case study of consumers at Mahkota Gold Shop. The type of research used is quantitative with the research method used is a survey with a questionnaire as a data collection tool. This research has met the requirements for validity, reliability and normality. The data analysis used in this research is the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination test. The research results show that product variety, word of mouth, and lifestyle have a significant influence on interest in buying gold. Keywords: Product Variations, Word of Mouth, Lifestyle, Purchase Interest